PENYELESAIAN SENGKETA PEMENUHAN HAK NAFKAH ANAK PASCA PERCERAIAN MELALUI MEDIASI DI PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK KOTA DUMAI - Rivanka Gradian Baldi; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the jurisdiction of the Dumai City Religious Court there are several divorce caseswhose decisions also decide on the father's obligation to provide child support rights. In caseNumber 399/Pdt.G/2018/PA.Dum, regarding the fulfillment of child maintenance rights by theDumai City Religious Court in its decision imposed the obligation to provide maintenance ofchildren to the father with the provisions as stated in the decision. Ironically, theimplementation of this decision cannot be carried out optimally. In fact, the father does notgive the right to provide for the child at all as has been decided by the Judge at the ReligiousCourt on the grounds that he cannot afford the amount of maintenance that must be given permonth, thus causing the child not to get the comfort and protection as the rights he has. Thepurpose of writing this thesis: First, to find out the Mediation Process for Fulfilling Post-Divorce Children's Livelihoods at the Dumai City Women and Children EmpowermentIntegrated Service Center.Second, to find out the Dispute Resolution of the Fulfillment of Post-Divorce Children'sLivelihoods through Mediation at the Dumai City Women and Children EmpowermentIntegrated Service Center.The type of research used in this legal research is sociological legal research. Analysisof the data used is the author to analyze data qualitatively. In drawing conclusions the authoruses the deductive thinking method, namely a way of thinking that draws conclusions from ageneral statement or argument into a specific statement.From the research results, there are two main things that can be concluded. First, themediation process at the Dumai City Integrated Service Center for Women and Children hasgone well, it's just that the results of the agreement did not work as it should. Ironically, theimplementation of this decision cannot be carried out optimally. Second, the handling ofchildcare cases at the Integrated Service Center for the Empowerment of Women and Childrenin the City of Dumai is an activity carried out in an effort so that children who are victims oftheir parents' divorce, have their rights fully fulfilled without prejudice to justice for bothparents. The handling of child rearing cases is handled by mediation, namely by bringingtogether the two parties, namely ex-husbands and ex-wives accompanied by the Institution.Keywords: Dispute resolution - Children and women - Divorce